Femtosecond laser-generated high-energy-density states studied by x-ray FELs. (27th October 2016) - Nakatsutsumi, M; Appel, K; Baehtz, C; Chen, B; Cowan, T E; Göde, S; Konopkova, Z; Pelka, A; Priebe, G; Schmidt, A; Sukharnikov, K; Thorpe, I; et al.
Abstract: The combination of powerful optical lasers and an x-ray free-electron laser (XFEL) provides unique capabilities to study the transient behaviour of matter in extreme conditions. The high energy density science instrument (HED instrument) at the European XFEL will provide the experimental platform on which an unique x-ray source can be combined with various types of high-power optical lasers. In this paper, we highlight selected scientific examples together with the associated x-ray techniques, with particular emphasis on femtosecond (fs)-timescale pump–probe experiments. Subsequently, we present the current design status of the HED instrument, outlining how the experiments could be performed. First user experiments will start at the beginning of 2018, after which various optical lasers will be commissioned and made available to the international scientific community.